Optimisation of processes of logistics companies in tender placement of orders - E. L. Tcai (Вестник университета, 2025)
The article considers the problem of the occurrence of implicit costs for logistics companies during the tender placement of orders using the example of courier services. All actions of the logistics companies are presented in the form of diagrams of processes and decomposed subprocesses using the tools of the process approach, namely, grapho-analytical methods. Thus, discrete event processes are displayed in the IDEF0 (Integrated Definition) notation. An analysis of subprocesses is conducted and a cost concentration zone with signs of implication is identified. The negative impact of the implication on the usefulness for logistics companies of participating in the tender placement of orders is determined. In the article, implicit costs are understood as transaction and opportunity costs that arise during the implementation of the tender process of placing an order of logistics companies on electronic platforms. The work also analyses patterns and dynamics of these two type of costs when economic agents and counterparties enter into relationships. At the same time, it is necessary to fulfill the tasks of preserving the reputation of the customer agent, reducing the risk of losing the supplier agent, and concluding a contract on favourable terms. To solve the objectives set in the article, theoretical aspects based on new trends in understanding the fundamentals of institutional economics are used.